Immunochemical characterization of inhibitory mouse cortical neurons: Three chemically distinct classes of inhibitory cells - Xu, Xiangmin (2010)
The cerebral cortex has diverse types of inhibitory neurons. In rat cortex, past research has shown that parvalbumin (PV), somatostatin (SOM), calretinin (CR), and cholecystokinin (CCK) label four distinct chemical classes of GABAergic interneurons. However, in contrast to rat cortex, previous studies indicate that there is significant co-localization of SOM and CR in mouse cortical inhibitory neurons. In the present study, we further characterized immunochemical distinctions among mouse inhibitory cortical neurons by double immunochemical labeling with chemical markers. We found that, PV, SOM and vasointenstinal peptide (VIP) reliably identify three non-overlapping distinct subpopulations, as there was no overlap of immunoreactivity between PV and all the other chemical markers tested, and SOM and VIP did not show any overlap in labeled neurons in all the cortical areas. In comparison, there was significant overlap in combinations of other chemical markers. With some laminar and regional variations, the average overlap of SOM/CR (percentage of SOM+ cells expressing CR) and SOM/neuropeptide tyrosine (NPY) across all examined layers and cortical regions was 21.6% and 7.1%, respectively. The average overlap of VIP/CR, VIP/NPY, and CR/NPY was 34.2%, 9.5% and 10%, respectively. We quantified and assessed the percentages of marker-positive GABAergic cells, and showed that the non-overlapping subpopulations (i.e., PV+, SOM+ and VIP+ cells) accounted for about 60% of the GABAergic cell population. Taken together, our data reveal important chemical distinctions between mouse inhibitory cortical neurons and indicate that PV, SOM, and VIP can differentially label a majority of mouse inhibitory cortical neurons.